Whales from space: Four mysticete species described using new VHR satellite imagery. Issue 2 (27th October 2018) - Cubaynes, Hannah C.; Fretwell, Peter T.; Bamford, Connor; Gerrish, Laura; Jackson, Jennifer A.
Abstract: Large‐bodied animals such as baleen whales can now be detected with very high resolution (VHR) satellite imagery, allowing for scientific studies of whales in remote and inaccessible areas where traditional survey methods are limited or impractical. Here we present the first study of baleen whales using the WorldView‐3 satellite, which has a maximum spatial resolution of 31 cm in the panchromatic band, the highest currently available to nonmilitary professionals. We manually detected, described, and counted four different mysticete species: fin whales ( Balaenoptera physalus ) in the Ligurian Sea, humpback whales ( Megaptera novaeangliae ) off Hawaii, southern right whales ( Eubalaena australis ) off Península Valdés, and gray whales ( Eschrichtius robustus ) in Laguna San Ignacio. Visual and spectral analyses were conducted for each species, their surrounding waters, and nonwhale objects ( e.g ., boats). We found that behavioral and morphological differences made some species more distinguishable than others. Fin and gray whales were the easiest to discern due to their contrasting body coloration with surrounding water, and their prone body position, which is proximal to the sea surface ( i.e ., body parallel to the sea surface). These results demonstrate the feasibility of using VHR satellite technology for monitoring the great whales.